An enhanced sensitivity RF energy harvester system using tunnel FET based rectifier - Selvan, Saravana; Wei, Suen; l, Umaya; R, Gobbi.; Zaman, Mukter (International Journal of Engineering and Technology, 2018)
Radio Frequency (RF) energy harvesting system is a viable solution for powering ultra-low power sensors as long as there is minimal am-bient power that exists around it. However, at very low ambient RF level or under sub-milliwatt (< -20 dBm) level conditions, the RF recti-fier in the harvester system shows very poor performance and probably fails to convert RF signal into DC output voltage. This is due to the sub-threshold voltage limits or weak sensitivity of the rectifying device used in the rectifier. However, to actively operate it in sub-milliwatt level RF input, this research proposes a band-to-band tunneling behavior of Tunnel FET (TFET) device. The steep slope characteristic of TFET contributes in improving the sensitivity, output voltage, and power conversion efficiency (PCE). Keysight Advanced Design System (ADS) software is used to conduct a simulation study on our proposed idea. An LC matching network is also designed using the smith chart tool to achieve maximum sensitivity. The proposed concept achieved a maximum sensitivity of -60 dBm at UHF of 900 MHz and produced an output voltage of 350 mV at -25 dBm. A maximum PCE of 70% at -39 dBm is obtained in the 3 stage voltage multiplier.